2020
DOI: 10.1051/kmae/2020026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anthropogenic transformations on the vegetation of selected abiotic types of rivers in two ecoregions (Southern Poland)

Abstract: The quality of water in rivers is declining worldwide due to anthropogenic activities. This phenomenon may be exacerbated by climate change and population growth. We hypothesised that both physical and chemical parameters of water, which reflect the differences in the underlying geology and anthropogenic transformations, are the most important characteristics to explain the distribution of macrophytes in rivers. In the present study, we analysed the effect of anthropogenic transformation on the structure of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…, 2010 ) as well in lowland rivers and ditches of southern England (Riley et al, 2018 ; Williams et al, 2004 ). More macrophyte species have been observed in lowland streams in north-western Europe (Baatrup-Pedersen et al, 2006 ; Halabowski & Lewin, 2020 ). In general, the diversity of macrophyte communities in natural and modified watercourses is the result of the synergistic effect of environmental and anthropogenic factors.…”
Section: Resultsmentioning
confidence: 99%
“…, 2010 ) as well in lowland rivers and ditches of southern England (Riley et al, 2018 ; Williams et al, 2004 ). More macrophyte species have been observed in lowland streams in north-western Europe (Baatrup-Pedersen et al, 2006 ; Halabowski & Lewin, 2020 ). In general, the diversity of macrophyte communities in natural and modified watercourses is the result of the synergistic effect of environmental and anthropogenic factors.…”
Section: Resultsmentioning
confidence: 99%
“…Hrivnak et al [ 47 ] report that macrophyte community composition in Slovak streams is affected by sediment type, riparian vegetation due to shade of woody vegetation, water depth, NO 2 level and pH. Halabowski and Lewin [ 20 ] showed that conductivity, altitude, land use adjacent to the rivers, and the proportion of sand were the most important factors that affected the distribution of macrophytes in rivers in southern Poland. However, Lewin and Szoszkiewicz [ 13 ] showed that non-nutrient parameters play an important role in determining macrophyte presence even in rivers with a relatively high input of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Their role is especially important in lowland watercourses since they increase the variability of habitats and physical conditions in a river [ 18 ]. In watercourses flowing through an agricultural landscape, macrophyte assemblages are well developed since these watercourses usually have poorly developed riparian zones and high input of nutrients [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the oristic study, semi aquatic and marshland plant species in the wetlands were mainly herbaceous and shrubby and showed discoloration in patches throughout the wetland. According to Tsala et al, (1993) and Halabowski et al, (2020), the presence of metal pollutants in wastewater and other anthropogenic in uences constitute a stress factor for plants through their toxic effects on the photosynthetic process and membrane function. The decolouration of vegetation in this wetland could therefore be allied to excessive chemical elements from anthropogenic activities.…”
Section: Discussionmentioning
confidence: 99%